2023
DOI: 10.1126/sciadv.ade5706
|View full text |Cite
|
Sign up to set email alerts
|

Rhombohedral-stacked bilayer transition metal dichalcogenides for high-performance atomically thin CMOS devices

Abstract: Van der Waals coupling with different stacking configurations is emerging as a powerful method to tune the optical and electronic properties of atomically thin two-dimensional materials. Here, we investigate 3R-stacked transition-metal dichalcogenides as a possible option for high-performance atomically thin field-effect transistors (FETs). We report that the effective mobility of 3R bilayer WS 2 (WSe 2 ) is 65% (50%) higher than that of 2H WS 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Second, interestingly, we find that the 3R-stacking bilayer WS 2 exhibits better electrical performance than the 2H-stacking bilayer WS 2 , which may be attributed to the both different intrinsic carrier mobility caused by interlayer coupling [18] and distinct contact resistances. We compared the electrical performance of 3Rand 2H-stacking bilayer WS 2 with other works, [20,[32][33][34][35][36][37][38][39] and found that our bilayer WS 2 shows a comparable on/off ratio and good mobility (Figure 4f and Table S2, Supporting Information). It is acknowledged that the electrical performance of 2D nanoplatesbased devices is determined by the intrinsic carrier mobility of the 2D materials and extrinsic parameters such as contact resistance, parasitic capacitance, and leakage current.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Second, interestingly, we find that the 3R-stacking bilayer WS 2 exhibits better electrical performance than the 2H-stacking bilayer WS 2 , which may be attributed to the both different intrinsic carrier mobility caused by interlayer coupling [18] and distinct contact resistances. We compared the electrical performance of 3Rand 2H-stacking bilayer WS 2 with other works, [20,[32][33][34][35][36][37][38][39] and found that our bilayer WS 2 shows a comparable on/off ratio and good mobility (Figure 4f and Table S2, Supporting Information). It is acknowledged that the electrical performance of 2D nanoplatesbased devices is determined by the intrinsic carrier mobility of the 2D materials and extrinsic parameters such as contact resistance, parasitic capacitance, and leakage current.…”
Section: Resultsmentioning
confidence: 86%
“…This feature will lead to the non-uniformity in optical and electrical properties. [20,21] Further exploration to obtain bilayer materials with controlled and tunable stacking order is needed.…”
Section: Introductionmentioning
confidence: 99%
“…show respective WSe 2 crystals with ML (light color) and bilayer regions (darker color) in 2H and 3R configurations, characterized by 60 • and 0 • rotational alignments of the upper WSe 2 layer with respect to the base WSe 2 MLs respectively [15,21,24]. The corresponding atomic configurations are illustrated in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some differences between the WSe 2 2H and 3R bilayers are revealed by PL measurements: the different peak wavelengths (1565 and 1572 meV) and peak full width at half maximum (FWHM, 62 and 44 meV, for the 3R and 2H stacking respectively). For both stacking the stark decrease in intensity indicates that the PL is dominated by momentum-indirect transitions at room temperature, but temperature-dependent measurements are required to study the details of the possible optical transitions [21,24,27].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, monolayer WS 2 showcases advantageous characteristics, such as substantial optical absorption, a significant exciton binding energy, and high carrier mobility. Therefore, all these unique properties of monolayer WS 2 give birth to a collection of WS 2 -based optoelectronics, such as modulators, detectors, and light sources. …”
Section: Introductionmentioning
confidence: 99%